Differential Contribution of RNA Interference Components in Response to Distinct Fusarium graminearum Virus Infections - Yu, Jisuk; Lee, Kyung-Mi; Cho, Won Kyong; Park, Ju Yeon; Kim, Kook-Hyung (Journal of virology, 2018)
The mechanisms of RNA interference (RNAi) as a defense response against viruses remain unclear in many plant-pathogenic fungi. In this study, we used reverse genetics and virus-derived small RNA profiling to investigate the contributions of RNAi components to the antiviral response against Fusarium graminearum viruses 1 to 3 (FgV1, -2, and -3). Real-time reverse transcription-quantitative PCR (qRT-PCR) indicated that infection of Fusarium graminearum by FgV1, -2, or -3 differentially induces the gene expression of RNAi components in F. graminearum . Transcripts of the DICER-2 and AGO-1 genes of F. graminearum ( FgDICER-2 and FgAGO-1 ) accumulated at lower levels following FgV1 infection than following FgV2 or FgV3 infection. We constructed gene disruption and overexpression mutants for each of the Argonaute and dicer genes and for two RNA-dependent RNA polymerase (RdRP) genes and generated virus-infected strains of each mutant. Interestingly, mycelial growth was significantly faster for the FgV1-infected FgAGO-1 overexpression mutant than for the FgV1-infected wild type, while neither FgV2 nor FgV3 infection altered the colony morphology of the gene deletion and overexpression mutants. FgV1 RNA accumulation was significantly decreased in the FgAGO-1 overexpression mutant. Furthermore, the levels of induction of FgAGO-1 , FgDICER-2 , and some of the FgRdRP genes caused by FgV2 and FgV3 infection were similar to those caused by hairpin RNA-induced gene silencing. Using small RNA sequencing analysis, we documented different patterns of virus-derived small interfering RNA (vsiRNA) production in strains infected with FgV1, -2, and -3. Our results suggest that the Argonaute protein encoded by FgAGO-1 is required for RNAi in F. graminearum , that FgAGO-1 induction differs in response to FgV1, -2, and -3, and that FgAGO-1 might contribute to the accumulation of vsiRNAs in FgV1-infected F. graminearum . IMPORTANCE To increase our understanding of how RNAi components in Fusarium graminearum react to mycovirus infections, we characterized the role(s) of RNAi components involved in the antiviral defense response against Fusarium graminearum viruses (FgVs). We observed differences in the levels of induction of RNA silencing-related genes, including FgDICER-2 and FgAGO-1 , in response to infection by three different FgVs. FgAGO-1 can efficiently induce a robust RNAi response against FgV1 infection, but FgDICER genes might be relatively redundant to FgAGO-1 with respect to antiviral defense. However, the contribution of this gene in the response to the other FgV infections might be small. Compared to previous studies of Cryphonectria parasitica , which showed dicer-like protein 2 and Argonaute-like protein 2 to be important in antiviral RNA silencing, our results showed that F. graminearum developed a more complex and robust RNA silencing system against mycoviruses and that FgDICER-1 and FgDICER-2 and FgAGO-1 and FgAGO-2 had redundant roles in antiviral RNA silencing.